Impact of oil price on inflation, trade balance and economic growth in African OPEC member countries - Bala, Umar (2017)
This study examined the impact of oil price on inflation, trade balance and economic growth in African OPEC member countries. The study applied transmitted channels of oil price to various economic sectors as a theoretical framework. Moreover, this study used annual panel data of four African OPEC members namely Algeria, Angola, Libya and Nigeria ranging from 1995 to 2014. Within this period the African OPEC countries witnessed a rapid increase in economic growth as oil price increases, while decreases in oil price produce ambiguity. In addition, this study used three different proxies of oil price in the analysis namely specific spot oil price of individual countries, OPEC reference oil price and an average of Brent, Dubai and West Texas Intermediate (WTI) oil price. The first objective of this study is to explore the non-linear impact of oil price on inflation in African OPEC members. The inflation rate is usually volatile in response to oil price changes. The dynamic panels ARDL (PMG and MG models) were used to examine the short and the long-run impact of oil price changes on inflation. In the linear models, this study found that the long-run coefficient of oil price, money supply, exchange rate and GDP are positively encouraging inflation while food production negatively influenced inflation. We further estimated the model using NARDL specification which decomposing the oil price into positive and negative changes. In the nonlinear model, the study found that the positive and negative changes in oil price are positively encouraging inflation but the impact is larger when oil price dropped. Motivated by whether the the OPEC members can improve their trade balance via higher oil price or higher oil export, the second objective of this study examines the threshold effect of oil price on the trade balance in African OPEC members. Then, this study investigated the impacts of oil export as a substitute proxy of oil price on the trade balance models. The Panel fully modified OLS and dynamic OLS estimators to examine the long-run impact of oil price on import, export and trade balance. This study found that increase in oil price and oil export positively encourage import, export and trade balance while exchange rate depreciation significantly discourages import and insignificantly in export and trade balance models. From the results of trade balance, the study found that there is a threshold effect of oil export. Increase in oil export improves the trade balance when oil export is above a certain threshold. It is observed that economic growth of African OPEC members showed larger adjustment during the fall of oil price compared to the hike in oil price and this may due to different level of financial development. The third objective of this study investigates the threshold effect of oil price and financial development on economic growth in African OPEC members. The fully modified OLS and dynamic OLS were used to examine the long-run impact of oil price on economic growth. The findings portrayed that increases in oil price positively encourage economic growth and better financial development leads to higher economic growth in African OPEC countries. Based on the threshold results, the study found that the threshold effect of financial development is significant and has a larger impact when it is above the threshold. The policy implications from this study are: (1) The policy makers should use different policy between positive and negative oil price changes as shown that inflation is high when oil price decrease. The policy makers can use the contractionary monetary policy to reduce the inflation rate. In additiona, the government should encourage domestic food production both in quantity and quality in order to reduce inflation. (2) For those countries that are highly dependent on oil export, the government can increase oil export to improve the trade balance. (3) In promoting economic growth, the government can make necessary effort to benefit from higher oil prices but emphasize a need to encourage investing in financial services for stronger financial development, hence promote economic growth in African OPEC member countries.